Current Labour Market Challenges in the Light of Future Economic and Demographic Developments - Adriana GRENČÍKOVÁ; Jozef HABÁNIK; Jana ŠPANKOVÁ; Matej HÚŽEVKA; Martin ŠRÁMKA (European Journal of Interdisciplinary Studies, 2022)
Economic growth and GDP growth have been dramatically affected by the COVID-19 pandemic. Both indicators are the factors that decisively affect the situation in the labour market, which is currently facing major challenges. One of the challenges is aging population. The number of the working- age population is declining, which may also have a significant impact on GDP growth in the future. The main purpose of the study is to analyse past and predicted GDP growth rates and the past and predicted shares of the working age population in the selected economies. Based on the analyses, the study attempts to identify the factors that are able to stimulate GDP growth while the size of working age population is predicted to shrink in the future. In the opening section of the empirical part, a comparison of the GDP evolution in China, Russia, USA, India, Slovakia and the EU is presented. Subsequently, long-term GDP and demographic forecasts are presented. It follows from the analyses that it is necessary to introduce new technologies to replace the shrinking workforce if sustainable economic growth is to achieve.